Disbandment of Jemaah Islamiyah: the impact on militant groups - Noor Huda Ismail (2024)
The recent changes within Jamaah Ansharut Syariah indicate significant fractures and defections following the disbandment of Jamaah Islamiyah. The shifts, driven by external pressures and internal disillusionment, indicate a broader trend of disengagement from jihadist movements in Indonesia, potentially altering the regional security landscape.